1991
DOI: 10.1103/physrevlett.67.1986
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ionization ofC60andC70

Abstract: Delayed ionization with average lifetimes on the order of several //sec has been observed for twophoton 308-nm excimer laser ionization of C60 and C70.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(94 citation statements)
references
References 10 publications
2
92
0
Order By: Relevance
“…2, results from statistical electron emission from the ground electronic state of C 18 H 11 -. 26,[33][34][35][36][37] That is, excess internal energy statistically accumulates amongst certain modes leading to ejection of the most weakly bound electron. The properties, typical lifetimes (micro-to milliseconds), and mathematical description of thermionic emission have been well-reviewed in the aforementioned references.…”
Section: Thermionic Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, results from statistical electron emission from the ground electronic state of C 18 H 11 -. 26,[33][34][35][36][37] That is, excess internal energy statistically accumulates amongst certain modes leading to ejection of the most weakly bound electron. The properties, typical lifetimes (micro-to milliseconds), and mathematical description of thermionic emission have been well-reviewed in the aforementioned references.…”
Section: Thermionic Emissionmentioning
confidence: 99%
“…31,32 If such an anion is formed under isolated conditions, the total internal energy of the system remains above the neutral ground state and the system may statistically detach the most weakly bound electron on a microsecond to millisecond timescale -known as thermionic emission. [33][34][35][36][37] Alternatively, some internally-hot anions may liberate excess internal energy through photoemission processes or by unimolecular dissociation to yield a stable anion.Using pump-probe femtosecond spectroscopy we have recently shown that a conjugated quinone, menadione, 26 can very efficiently produce ground electronic state anions following photoexcitation (or electron capture) with energies up to 3 eV above-threshold and probably higher. In menadione, the , is partly for experimental reasons and because the electron affinity is larger while maintaining a similar π-system.…”
mentioning
confidence: 99%
“…Internal energies up to tens of eV, corresponding to temperatures of thousands of K, can be achieved by absorption of many photons and rapid conversion from electronic to vibrational excitation. These superheated neutral molecules are observed to undergo delayed ionization [2,3], fragmentation [4], and optical emission [5], the microscopic analogs of well-known macroscopic cooling processes like thermionic emission, evaporation, and blackbody emission, respectively [1]. Detection of superheated neutral C 60 via delayed ionization becomes very efficient once the internal energy reaches 35 -40 eV [1].…”
Section: Infrared Resonance Enhanced Multiphoton Ionization Of Fullermentioning
confidence: 99%
“…In addition, delayed ionization sets in. 23 In the present work we report on a systematic two-color pump-probe mass-spectrometric study of the characteristic time scales involved in the ionization and fragmentation dynamics of C 60 fullerenes. The basic idea is to mimic the effect of elongated pulses by a femtosecond pump-probe approach with variable time delay between the pulses.…”
Section: Introductionmentioning
confidence: 99%